Students' perceptions of competency-based learning environment during COVID-19: a mixed-methods approach - Alkhurayyif, Yazeed (Frontiers in Computer Science, 2023)
The COVID-19 pandemic has had many reflections on teaching and learning. Competency-based learning (CBL) is outcome-based learning that supports students to focus on competencies and improve their learning skills. It was helpful for the universities during the pandemic to offer an effective online learning environment for computer science students. This study evaluated the CBL experience from the perspective of computer science students. The study used a mixed-methods approach and obtained data from 104 participants using an online questionnaire and in-person interviews. The study's findings indicated that the quality of the teacher, the learning environment, time management, and the expectations positively influenced student satisfaction, which in turn positively influenced students' performance. The investigation found statistically significant evidence that the CBL was helpful for students' skill improvement. Additionally, this study presented the challenges and limitations of CBL, which can inform universities and course developers to improve the standards of CBL. Using this study's implications, academic researchers can extend their research to develop innovative approaches for the CBL environment.